1990
DOI: 10.1037/0003-066x.45.6.721
|View full text |Cite
|
Sign up to set email alerts
|

Graduate training in statistics, methodology, and measurement in psychology: A survey of PhD programs in North America.

Abstract: Preliminary versions of the results of the survey and the commentary were presented in L. S. Aiken and S. G. West (chairs), Adequacy of Methodological and Quantitative Training: Perspectives of the Disciplines,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
242
1
8

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 226 publications
(259 citation statements)
references
References 42 publications
(25 reference statements)
4
242
1
8
Order By: Relevance
“…Twenty-three of the 27 universities with QM programs responded for a response rate of 85%. This rate is consistent with that reported by Aiken et al (1990) and Guo and Nitko (1996). We believe that this response rate is large enough to generate credible results, although it is possible that there is some unknown but systematic difference between QM faculty members who responded to the survey and those who did not respond.…”
Section: Sampling Proceduressupporting
confidence: 83%
See 4 more Smart Citations
“…Twenty-three of the 27 universities with QM programs responded for a response rate of 85%. This rate is consistent with that reported by Aiken et al (1990) and Guo and Nitko (1996). We believe that this response rate is large enough to generate credible results, although it is possible that there is some unknown but systematic difference between QM faculty members who responded to the survey and those who did not respond.…”
Section: Sampling Proceduressupporting
confidence: 83%
“…8 In terms of demographics, Aiken et al (1990) found that 89% of the departments offered an introductory graduate statistics sequence, and of the departments offering this sequence, 77% were one year in length. A minority of institutions --17% --offered doctorates in a quantitative area of specialization, although one-third of these did not have any first-year students.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations